Jak zachęcić nauczycieli do dbania o własny dobrostan? Wnioski z wdrożenia programu „Dobrostan w Szkole” - Ilczuk, Ewa; Mykowska, Aleksandra; Ziętek, Dorota (Kultura-Społeczeństwo-Edukacja, 2024)
Teachers are a professional group with elevated stress levels. Moreover, in recent years they have faced the challenge of adapting to conditions caused by global crises. A training program “Well-being at School” aimed at supporting teachers’ resilience has been developed. The program includes a range of support methods based on various approaches (multi-theoretical framework), including positive psychology, poly-vagal theory and mindfulness. The paper presents the main principles of the program, followed by the results of a study aimed at verifying its effectiveness. 48 teachers participated in the study, 28 of whom ac-tively participated in the program, while 20 constituted the comparison group. The respondents complet-ed a questionnaire containing the CD-RISC resilience scale and additional questions related to well-being twice, five months apart. Analyses showed no significant increase in participants’ levels of psychological resilience, while they did show changes in attitudes related to caring for well-being. The results provide conclusions that are valuable from the perspective of designing interventions to support mental health.